2022
DOI: 10.3390/en16010387
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Liquid Metal Turbulent Heat Transfer in Cross-Flow Tube Banks

Abstract: Heavy liquid metals (HLM) are attractive coolants for nuclear fission and fusion applications due to their excellent thermal properties. In these reactors, a high coolant flow rate must be processed in compact heat exchangers, and as such, it may be convenient to have the HLM flowing on the shell side of a helical coil steam generator. Technical knowledge about HLM turbulent heat transfer in cross-flow tube bundles is rather limited, and this paper aims to investigate the suitability of Reynolds Average Navier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The tube bundles were subjected to a constant heat flux of 20,000 W/m 2 to maintain thermal conditions akin to the experiment conducted by Ref. [ 16 ]. No-slip condition is applied to the walls, excluding the front and back walls where the symmetry boundary condition is proposed.…”
Section: Physical Model and Cases Consideredmentioning
confidence: 99%
See 1 more Smart Citation
“…The tube bundles were subjected to a constant heat flux of 20,000 W/m 2 to maintain thermal conditions akin to the experiment conducted by Ref. [ 16 ]. No-slip condition is applied to the walls, excluding the front and back walls where the symmetry boundary condition is proposed.…”
Section: Physical Model and Cases Consideredmentioning
confidence: 99%
“…They found that due to the intensified turbulence intensity and generation of transverse flow, the highest Nu and friction factor ( f ) is achieved for a helix angle of 45°. The thermal behaviour of LBE in the inline and staggered arrangement was studied by Tassone et al [ 16 ]. They concluded that the steady k −ω SST model combined with the varying turbulent Prandtl number model resulted in the most accurate numerical model.…”
Section: Introductionmentioning
confidence: 99%